Korupsi Versus Hibah dan Hadiah Perspektif Hukum Islam - Salsabila, Shabrina Syifa; Shuhufi, Muhammad; Amin, Abd. Rauf Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study attends to analyze the ulama’s perspective regarding the corruption, gift and grants, as well as the actions taken to prevent corruption, discusses the issue of corruption that occurs in human life. However, the problem is how the grants and gifts given to certain parties are categorized as corruption. This research is library research which is analyzed with a qualitative approach with national law and Islamic law perspectives. The results showed that from the point of view of Islamic law, people's insights were very limited to the issue of bribes and rewards. Some people think that bribery is not a crime, but only a small mistake. Some others, even so, that bribes are forbidden, but they do not care about the prohibition, let alone because they get the benefits. On the other hand, society perceives the bribe as a gift or a token of gratitude. Some even think of it as money for the help someone has given, so they don't feel it as a mistake or even a crime.